ANALISIS PERILAKU KOMPLAIN KONSUMEN PADA KOLOM "REDAKSI YTH" SURAT KABAR KOMPAS PERIODE 1-31 MARET 2004 - Siti Rahayu (Journal of Management and Business, 2004)
Every consumers that have problems need a solution, so companies should deliver a valuable product and minimize the problems. Some companies did not realize the importance of customer complain handling to deliver customer satisfaction. This study attemp to describe one of the customer complain "form" which is newspaper public complain to third party. This form of complain has a lot of information for companies, although not all of company notice. This study also shown that consumer complain is the result of accumulative disappointment to the product/company that has not been resolve.